Transformasi Palembang Menuju Kota Multikultural: Sebuah Refleksi terhadap Naskah Undang-Undang Simbur Cahaya dan Tuhfah ar-Raghibin - Wirajaya, Asep Yudha (IAIN Surakarta, 2018)
History has recorded Palembang as a multiethnic city capable of developing into the capital of the Maritime kingdom. Of course, this success can not be separated from the participation of leaders and stakeholders who have struggled for their vision to be achieved. This is reflected in the text